Lipid, blood pressure and kidney update 2013 - Banach, Maciej (Springer Netherlands, 2014)
The year 2013 proved to be very exciting as far as landmark trials and new guidelines in the field of lipid disorders, blood pressure and kidney diseases. Among these are the International Atherosclerosis Society Global Recommendations for the Management of Dyslipidemia, European Society of Cardiology (ESC)/European Society of Hypertension Guidelines for the Management of Arterial Hypertension, American Diabetes Association Clinical Practice Recommendations, the Kidney Disease: Improving Global Outcomes Clinical Practice Guidelines for Managing Dyslipidemias in Chronic Kidney Disease (CKD) Patients, the American College of Cardiology/American Heart Association Guideline on the Treatment of Blood Cholesterol to Reduce Atherosclerotic Cardiovascular Risk in Adults, the Joint National Committee Expert Panel (JNC 8) Evidence-Based Guideline for the Management of High Blood Pressure in Adults, the American Society of Hypertension/International Society of Hypertension Clinical Practice Guidelines for the Management of Hypertension in the Community, the American College of Physicians Clinical Practice Guideline on Screening, Monitoring, and Treatment of Stage 1–3 CKD and many important trials presented among others during the ESC Annual Congress in Amsterdam and the American Society of Nephrology Annual Meeting—Kidney Week in Atlanta, GA. The paper is an attempt to summarize the most important events and reports in the mentioned areas in the passing year.